The microbiological and chemical characteristics of yoghurt incorporated with watermelon rind powder - Nur Aliah Shamsul Norazman,; Nurmahani Mohd Maidin,; Nor Akma Ismail,; Mohd Nizam Lani,; Yusnita Hamzah,; Faiqa Shazeaa Mohd Salleh,; Nur Suaidah Mohd Isa, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Watermelon rind accounts for approximately one-third of the overall fruit mass. It is usually discarded due to its low commercial value. However, it is reported to contain valuable nutrients and is an effective source of pectin that can act as a potential prebiotic. This study aimed to study the effects of watermelon rind powder (WRP) on the growth of probiotic bacteria in yoghurt and its chemical characteristics. Watermelon rind was dried by using a dehydrator and ground into powder form before being incorporated into fresh yoghurt at 2% and 4% w/v. A sample with 0% w/v WRP was prepared as control. The effect of WRP on the growth of probiotic bacteria was determined by MRS plate count. Chemical analyses including titratable acidity, pH and Brix were conducted during the fermentation process. The results showed that the increase in WRP percentage resulted in a significant increase in bacterial growth with 7.20 ± 0.22 log CFU/mL for the control sample as compared to 8.42 ± 0.23 log CFU/mL for sample with 4% WRP after 30 hr of incubation. The fermentation time was also improved with the presence of WRP with a 0.22 h-1 increase in growth rate observed for the sample with 4% WRP as compared to the control sample. Furthermore, samples containing 4% WRP showed the highest increment in titratable acidity (12.47) and the highest percentage in Brix value reduction (51.04%) during the fermentation period as compared to the control sample. Biochemical analysis showed negative values for oxidase and catalase test while positive values were obtained for gram-staining indicating the presence of Lactic acid bacteria from the gram-positive group. This study demonstrates the high potential of WRP in promoting bacterial growth for yoghurt production which is beneficial to the food industry other than promoting the ongoing effort of food waste reduction.